Model for Increasing the Brilliance and Quality of Education Based on Total Quality Management: Empirical Study at the Semarang Police Academy - Marpaung, Irfan Satya Prasaja; Prajanti, Sucihatiningsih Dian Wisika; Pramono, Suwito Eko; Hidayah, Isti (Journal of Ecohumanism, 2024)
This research aims to develop a model for improving educational quality excellence based on Total Quality Management (TQM): Empirical study at the Semarang Police Academy. This research was carried out with a research and development (R & D) design from Borg and Gall. This research focuses on developing a management model to increase the brilliance and quality of education at the Semarang Police Academy. To obtain precise, accurate and objective data, the research data collected must be tested through a data validity test. The results of the research show that in an effort to improve the brilliance and quality of education, the Semarang Police Academy already has a model which is currently being used as a reference. However, the existing model of educational excellence and quality still has several weaknesses. This weakness is that the quality management process is not yet oriented towards current development conditions and is not yet based on comprehensive quality improvement management. The current model is still conventional and does not focus on quality and brilliant education. Overall, the education model at the Semarang Police Academy has led to increasing the brilliance and quality of education, but is still not optimal. In terms of the concept of brilliance and quality of education implemented by the Police Academy, the aspects of brilliance and quality of education have not been integrated so that they have not been able to improve the quality of education as a whole. The model developed in Improving the Brilliance and Quality of Education at the Semarang Police Academy was developed using a TQM approach. The success of TQM in education is positioning the product as the central point for achieving organizational goals and achievements. Quality in products will not be produced without quality control in the process. Quality in the process will not be guaranteed without proper and effective organization. A proper and effective organization is meaningless without adequate leaders. Commitment from all components of the organization, from bottom to top, is a supporting pillar for all other components. Each pillar depends on the other four pillars and if one is weak by itself the other pillars will also be weak. TQM in education is related to the creation of a culture of quality by placing customers as the main focus through the involvement of all employees and educational staff as well as continuous improvement, in order to achieve a quality educational organization, which is able to compete and survive in the current era of development.